Faktor Pemicu Konflik dan Resolusi Konflik Sebagai Upaya Meningkatkan Kinerja Karyawan Pada PT Lestari Djaya Utama - Adinda Septi Salsabila; Bambang Septiawan (Eco-Entrepreneur, 2022)
Every person in the company must have different characteristics from one another. It creates dissent so that it can create conflicts that can interfere with employee performance. The study aims to identify the underlying factors behind conflict and the impact it can have on workers ‘performance PT LESTARI JAYA UTAMA Desa Kendalrejo Talun. The data-gathering method USES an interview technique. Research has found a recurring conflict between employees and superiors, as there are frequent disagreements between employees and their superiors. This conflict profoundly affects the performance of employees, employees who experience conflict undoubtedly in the work will feel less energetic and always feel inadequate to do work, so workers performance is reduced. PT LESTARI DJAYA UTAMA Almost all have encountered conflict between employees and between employees. There must be a factor, both because of differences of opinion and lack of compliance with his or her department friends. The potential impact of this conflict of work will be the degeneration of workers’ performance. The conflict was eventually settled in a matter of deliberation between the parties.